Kajian Penerapan Teknologi Budidaya Tanaman Dan Produktivitas Padi Sawah (Oryza sativa L.) Di Kecamatan Dumoga - Rorong, Feibe; Tumewu, Pemmy; Pamandungan, Yefta (Sam Ratulangi University, 2024)
The objective of the study was to assess the application of crop cultivation technology and productivity of paddy rice in Dumoga District, Bolaang Mongondow Regency, North Sulawesi Province. The research was conducted from November to December 2022. The research was located in Dumoga District, Bolaang Mongondow Regency, North Sulawesi Province. This research was qualitative research by conducting surveys and interviews with 30 farmers in Dumoga Subdistrict using a prepared questionnaire, including the identity of farmers, farming conditions and cultivation techniques of paddy rice in Dumoga Subdistrict (North Mopugad Main Village, North Mopugad 1, North Mopugad, South Mopugad, South Mopugad 1, South Mopuya, and Amertabuana). The research location was determined by purposive sampling, namely Dumoga Sub-district, Bolaang Mongondow Regency, with the consideration that the area is the center of paddy rice production in North Sulawesi. The data analysis used was a qualitative descriptive analysis technique. The data obtained were then processed and tabulated in the form of tables and diagrams. The results showed that the application of paddy rice cultivation technology carried out by farmers in Dumoga District included the application of land preparation using a hand tractor, a single planting pattern, a direct seed planting system of direct seed planting (Tabela), the spacing used was 20×20 cm, fertilization using fertilizers (Urea, Phonska, TSP and SP36), water sources came from irrigation irrigation, pest control using pesticide active ingredients and harvesting already using harvesting machines, and paddy rice production in Dumoga District reached 4 tons of GKG, with a productivity of 1.6 tons/ha.